Pemanfaatan Media Pembelajaran Berbasis Teknologi Informasi Dalam Meningkatkan Minat Belajar Peserta Didik Di MTs Negeri Kota Bengkulu - Yuliza, Septi (Gayaku Publisher, 2023)
This study discusses the utilization of information technology-based learning media in increasing students' interest in learning at MTs Negeri Bengkulu City, this study aims to determine the utilization of information technology-based learning media in increasing students' interest in learning. The method used in the research uses a qualitative approach, while the research subjects are subject matter teachers who utilize information technology-based learning media in the learning process at MTs Negeri Bengkulu City, while the data collection techniques use interviews, observation, and documentation techniques. The results of the study found that, First, the implementation of learning by utilizing information technology-based learning media provides very good things, especially in terms of more practical learning utilization, more optimal time utilization and easier and varied material utilization. So that students are very enthusiastic in the learning process. Second, the utilization of information technology media has a positive impact on the learning process of students in increasing interest in learning in the learning process. Besides being fun, it can also generate motivation, enthusiasm in participating in learning in Madrasah. Third, from the results of interviews and observations made to students, by utilizing information technology-based learning media there is an increase in students' interest in learning. Learners are very motivated in participating in learning. The enthusiasm that arises in students because the materials and media used are more interesting, more active, effective and more varied learning.